Palm Aphid Cerataphis brasiliensis (Hempel) (Insecta: Hemiptera: Aphidae: Hormaphidinae) - Bonnie C. Wells (EDIS)
The palm aphids are the only aphids known to infest palm plants. High populations occasionally become severe in nurseries and the landscape and can cause substantial damage to young coconut palms. They pierce palm foliage and suck out the plant phloem content, causing yellowing of the tissues and loss of plant vigor. In addition, honeydew production by the aphids promotes sooty mold growth that can limit photosynthesis. Palms heavily infested with aphids can experience stunted growth. This 4-page fact sheet was written by Bonnie C. Wells and published by the UF Department of Entomology and Nematology, March 2012.